Enhancing Nazir Capacity through Legal Literacy of Land Trust to Ensure Legal Certainty in Waqf Land Management - Suhadi Suhadi; Dani Muhtada; Asmarani Ramli; Imam Baehaqie; Isnani; Ardi Sirajudin Rauf; Lucky Andinna Santyoko; Muhammad Ridha (Universitas Negeri Semarang, 2024)
Nazir as the party who received the mandate to receive and manage waqf land faced several problems related to waqf land. These problems are that the waqf land has not been certified, the waqf land is in dispute, the waqf land has been lost/controlled by another party. This problem occurs because the practice of waqf land is carried out verbally on the basis of mutual trust, the waqf pledge has not been made before PPAIW, the waqf pledge deed has not been processed, the waqf land has not been registered, and the waqf land has not been utilized according to the waqf pledge. Through community service activities, Nazir's capacity was increased through literacy in land waqf law. Legal literacy includes the land waqf process and waqf land registration. The legal act of donating land must be carried out according to the Waqf Law, carried out before an authorized official and the waqf land is registered at the Land Office. The waqf pledge must be made in front of the Waqf Pledge Deed Registrar to be recorded in the Waqf Pledge Deed. The Waqf Pledge Deed is written evidence in land registration at the Land Office, as the basis for issuing a Waqf Land Certificate. Waqf Land Certificates are issued to create legal certainty and legal protection for land waqf. The regulation of land waqf in the Waqf Law and its implementing regulations further confirms waqf as an important and useful institution for efforts to realize community welfare, in line with the goals of state life.